Immobility in Mobility during COVID-19: Reflections on ‘Being Stuck’ in the Home Country of an International Doctoral Student - Phan, Anh (Journal of International Students, 2022)
While international education has long been characterised by mobility, the Covid-19 pandemic has shifted our attention to immobility as thousands of international students have experienced immobility in various ways, one of which is being stuck in their home countries.  This paper records how such immobility entailed the feeling of confusion and detachment in an international doctoral student and her efforts to overcome physical immobility by making use of digital mobility. Through the sensemaking framework, this paper not only illuminates the consequences of disrupted mobility on an international doctoral student’s academic learning and sense of belonging but also highlights the student’ agency, which then offers a research area that may yield interesting insights in this unprecedented time of uncertainty.